Writing scientific research articles : - Cargill, Margaret (Wiley-Blackwell, 2009)
This book shows scientists how to apply their analysis and synthesis skills to overcoming the challenge of how to write, as well as what to write, to maximise their chances of publishing in international scientific journals.